National institutional context and voluntary carbon disclosure: An international study of the banking industry - Jamet, Benoît; Bousquet, Julien; Masse, Antoine (Management international / International Management / Gestiòn Internacional, 2024)
The determinants of banks’ voluntary environmental disclosure have been little studied in the literature. Drawing from the assumptions of institutional theory, this paper analyzes the impact of the national context, including the general legal system and the environmental policy of states, on banks’ carbon disclosure. Based on three international samples, the results show a positive relationship between the strength of the legal system (degree of law enforcement), the stringency of environmental regulations, environmental performance, and the quality of banks’ carbon disclosure.